Can High Mobility Group Box 1 Protein Predict Ongoing Subclinical Inflammation in Patients With Familial Mediterranean Fever? - Betül Öztürk; Esra Baskın; Kaan Gülleroğlu; Begüm Avcı; Nilüfer Bayraktar; Feride İffet Şahin (Galenos Publishing House, 2023)
Objective: Familial Mediterranean fever (FMF) is an autoinflammatory disease that commonly presents with fever, peritonitis, and pleuritis. Recent studies have reported ongoing inflammation in the attack-free period of patients with FMF. High mobility group box protein (HMGB1) is a frequently investigated marker with a strong diagnostic and prognostic role for several chronic inflammatory diseases. The objective of this study was to evaluate the role of HMGB1 in patients with FMF. Method: This cross-sectional study included a total of 57 (25 female/32 male) consecutive patients with FMF and a control group of 60 (30 female/30 male) healthy children. Demographic and clinical data of the patients were recorded. Blood samples were obtained from participants for HMGB1 analysis. Results: The median age of the patients was 123 months. The median follow-up time of patients was 5 years. There was no statistically significant difference between the patient and control groups in terms of age, sex, and body weight. The most frequent MEFV gene mutation was M694V (78%). HMGB1 was higher in the patient group than in the control group (p=0.001). The levels of HMGB1 were not different between the attack and the attack-free period (p>0.05). Conclusion: HMGB1 is significantly higher in FMF patients independent from being in the attack period. HMGB1 may demonstrate the ongoing subclinical inflammation in patients with FMF.